Subverting children’s literature: A feminist approach to reading Angela Carter - NEIMNEH, S.S.; AL-ZOUBI, N.A; AL-KHALILI, R.K (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article argues the importance of the short stories of Angela Carter to the field of children’s literature and its current adaptations. It looks at two of her stories. The result is fiction building on some patterns of children’s literature yet with a feminist tinge that questions the foundations of patriarchy. Her stories do not simply reverse patriarchy but subvert it from within. Sexual victimization and complicity in one’s oppression might be harmful, Carter seems to argue, but equally harmful is the underlying sexual slant of the popular fairy tales told/taught to children and instilling patriarchal values. RESUMEN Este artículo argumenta la importancia de los cuentos de Angela Carter en el campo de la literatura infantil y sus adaptaciones actuales. Mira dos de sus historias. El resultado es que la ficción se basa en algunos patrones de literatura infantil pero con un matiz feminista que cuestiona los fundamentos del patriarcado. Sus historias no solo revierten el patriarcado sino que lo subvierten desde adentro. La victimización sexual y la complicidad en la opresión de uno pueden ser perjudiciales, parece argumentar Carter, pero igualmente perjudicial es la inclinación sexual subyacente de los populares cuentos de hadas contados / enseñados a los niños e inculcando valores patriarcales.